Radiographic Fractal and Clinical Resonance Frequency Analyses of Posterior Mandibular Dental Implants: Their Possible Association With Mandibular Cortical Index With 12-Month Follow-up - Tözüm, Tolga F; Dursun, Erhan; Uysal, Serdar (Implant dentistry, 2016)
The aim of the present study was to investigate whether the mandibular cortical index (MCI) has a relationship with fractal dimension of bone and/or implant stability, and to justify the possible association between MCI, fractal dimension, and stability. Eighty-two subjects who received dental implants to replace missing mandibular premolar/molar sites were selected. Three months after surgical placement, implants were restored with fixed ceramic fused metal crowns. MCI was evaluated at baseline; fractal dimensions were measured with fractal analysis (FA) and implant stability quotient (ISQ) with resonance frequency analysis immediately after surgery and 12-month follow-up. FA at mesial and distal regions for Class 1, Class 2, and Class 3 MCI resulted with significant increases at 12-month follow-up compared to baseline. The ISQ in patients with Class 2 and Class 3 MCI resulted with a significant decrease compared to Class 1 MCI at baseline and at 12 months. All MCI classes evaluated with ISQ and FA at baseline values resulted with significant increases at 12 months. Significant correlations were considered for all mandibular posterior implants between baseline and 12-month measurements for ISQ and FA evaluations. Fractal analysis may be a useful method for understanding the healing process around implants and implant stability quotient values. Mandibular cortical index evaluations should be considered before implant procedures, which may provide a presurgical treatment plan and may provide information about the mandibular bone quality.